Chromium(VI) Catalyzed Oxidation of Primary Alcohol by Polymer Supported Reagent: A Kinetic and Mechanistic Approach - Y. Sonawane, Vilas (Asian Journal of Chemistry, 2013)
The kinetic of chromium(VI) catalyzed oxidation of 1-phenyl ethanol has been studied by the rate of disappearance of [Cr(VI)]. The reaction is zero order with respect to [Cr(VI)]. The reagent supported on anion exchange resin was found to be more efficient in the oxidation reaction. The reagent is very easily separated from the reaction mixture and can be manually removed from the reaction mixture, which remains clear during and after the reaction. The kinetic of oxidation of 1-phenylethanol with chromic acid supported on anion exchange resin like Amberjet-4400 [Cl–] in 1,4-dioxane has been studied. The reaction is found to be of zero order each in concentration of alcohol and oxidant. The reaction constants involved in the mechanism and the activation parameters have been calculated. There is a good agreement between observed and calculated rate constants under different experimental conditions. Acetophenone was detected as end product.